تصميم وإختبار نظام هيدروليكي يعمل على تنظيم الضغط من خلال صمامات الفائض في مضخة مكبسية - النجار, رائد; حمودة, محمد (Latakia University Journal -Engineering Sciences Series, 2016)
تمّ في هذا البحث وصف سلوك الصمام من خلال النموذج الرياضي لصمام تصريف الضغط ومن ثم دراسة تردد الاهتزازات الخاصة بالنظام الهيدروليكي وقد رسمت دورة الضغط في فترة قصيرة للمضخة المكبسية بغياب وبوجود صمام تصريف الضغط، أظهرت نتائج هذه الدراسة علاقة تردد الاهتزازات الخاصة لصمام تصريف الضغط والنظام الهيدروليكي حيث إن هذه العلاقة يمكنها أن تقرر فعالية حماية النظام قل التحميل, تبين أن معامل الضغط الديناميكي بغياب صمام تصريف الضغط j1 = 110% بينما بوجود الصمام يكون j2 = 20%. In this research, we described the behaviour of the valve by a mathematical model of the discharge pressure valve and then we studied the vibrations frequency of the hydraulic system which has plotted the pressure in a short period of piston pump in absence and in presence of discharge pressure valve. The results of this study showed special vibrations frequency relationship of the discharge pressure valve and hydraulic system where this relationship could decide the effectiveness of the protection system before loading. It also showed that dynamic pressure factor in absence of discharge pressure valve is j1=110% while the presence of the valve is j2 = 20%.